Implantation of a multifocal toric intraocular lens with a surface-embedded near segment after repeated LASIK treatments - Khoramnia, Ramin; Auffarth, Gerd U.; Rabsilber, Tanja Marina; Holzer, Mike P. (Journal of cataract and refractive surgery, 2012)
We report a 66-year-old patient who presented with increasing hyperopia, astigmatism, and presbyopia in both eyes 8 years after bilateral laser in situ keratomileusis (LASIK) and LASIK enhancement in the left eye aiming for spectacle independence. Bilateral multifocal toric Lentis Mplus intraocular lenses (IOLs) with an embedded near segment and individually customized cylinder correction were implanted uneventfully following phacoemulsification. The Haigis-L formula after previous hyperopia correction was chosen for IOL power calculation and provided reliable results. Emmetropia was targeted and achieved. Three months postoperatively, the uncorrected distance visual acuity had increased from 0.40 logMAR to 0.10 logMAR in the right eye and from 0.20 logMAR to 0.00 logMAR in the left eye. The patient gained 6 lines of uncorrected near visual acuity: 0.20 logMAR in the right eye and 0.10 logMAR in the left eye. This case shows that customized premium IOL implantation can provide accurate results even in challenging cases.Financial Disclosure The International Vision Correction Research Centre, Department of Ophthalmology, University of Heidelberg, Heidelberg, Germany, has received research grants, lecture fees, and travel reimbursement from Oculentis GmbH.
Gesehen am 20.08.2018